Analisis Peran Lembaga Zakat dalam Pemberdayaan Mahasiswa di Indonesia dan Malaysia - Rafsyanzanni, Adha Muhammad; Fahrullah, A'rasy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the role of zakat, infaq, and alms institutions in supporting educational access for underprivileged students, through a comparative study between the Muhammadiyah Zakat, Infaq, and Shadaqah Institution (LAZISMU) KLL UMSIDA East Java and ZAWAF UiTM Shah Alam, Malaysia. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that both institutions contribute to easing the burden of educational costs for students from the asnaf class. LAZISMU KLL UMSIDA distributes assistance in the form of a Single Tuition Fee (UKT) reduction through the Sang Surya scholarship program, which is given to internal students with certain economic conditions. Meanwhile, the Zakat, Alms and Waqf Division (ZAWAF) UiTM provides various forms of assistance, not only tuition fee reductions, but also college or dormitory fee assistance, monthly living assistance, religious study fees, and even health assistance. The ZAWAF approach shows a broader scope of support and addresses the basic needs of students. This study used primary data obtained through interviews with six informants: daily staff, scholarship recipients, and economic experts. The study concluded that zakat institutions play a crucial role in ensuring the sustainability of students' studies and recommended that zakat institutions in Indonesia begin developing more comprehensive and integrated aid models.